Treatment After Anterior Cruciate Ligament Injury: Panther Symposium ACL Treatment Consensus Group. Issue 6 (23rd June 2020) - Diermeier, Theresa; Rothrauff, Benjamin B.; Engebretsen, Lars; Lynch, Andrew D.; Ayeni, Olufemi R.; Paterno, Mark V.; Xerogeanes, John W.; Fu, Freddie H.; Karlsson, Jon; Musahl, Volker; Brown, Charles H.; et al.
Treatment strategies for anterior cruciate ligament (ACL) injuries continue to evolve. Evidence supporting best-practice guidelines for the management of ACL injury is to a large extent based on studies with low-level evidence. An international consensus group of experts was convened to collaboratively advance toward consensus opinions regarding the best available evidence on operative versus nonoperative treatment for ACL injury. The purpose of this study was to report the consensus statements on operative versus nonoperative treatment of ACL injuries developed at the ACL Consensus Meeting Panther Symposium 2019. There were 66 international experts on the management of ACL injuries, representing 18 countries, who were convened and participated in a process based on the Delphi method of achieving consensus. Proposed consensus statements were drafted by the scientific organizing committee and session chairs for the 3 working groups. Panel participants reviewed preliminary statements before the meeting and provided initial agreement and comments on the statement via online survey. During the meeting, discussion and debate occurred for each statement, after which a final vote was then held. Ultimately, 80% agreement was defined a priori as consensus. A total of 11 of 13 statements on operative versus nonoperative treatment of ACL injury reached consensus during the symposium. Overall, 9 statements achieved unanimous support, 2 reached strong consensus, 1 did not achieve consensus, and 1 was removed because of redundancy in the information provided. In highly active patients engaged in jumping, cutting, and pivoting sports, early anatomic ACL reconstruction is recommended because of the high risk of secondary meniscal and cartilage injuries with delayed surgery, although a period of progressive rehabilitation to resolve impairments and improve neuromuscular function is recommended. For patients who seek to return to straight-plane activities, nonoperative treatment with structured, progressive rehabilitation is an acceptable treatment option. However, with persistent functional instability, or when episodes of giving way occur, anatomic ACL reconstruction is indicated. The consensus statements derived from international leaders in the field will assist clinicians in deciding between operative and nonoperative treatment with patients after an ACL injury.